2016
DOI: 10.3390/ma9040253
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Bendable Circuits on a Polydimethylsiloxane (PDMS) Surface by Inkjet Printing Semi-Wrapped Structures

Abstract: In this work, an effective method was developed to fabricate bendable circuits on a polydimethylsiloxane (PDMS) surface by inkjet printing semi-wrapped structures. It is demonstrated that the precured PDMS liquid film could influence the depositing morphology of coalesced silver precursor inkjet droplets. Accordingly, continuous and uniform lines with a semi-wrapped structure were fabricated on the PDMS surface. When the printed silver precursor was reduced to Ag nanoparticles, the fabricated conductive film e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…The Dimatix inkjet printer requires a fluid with viscosity between 10–12 cP at jetting temperature; therefore, the mixture is diluted according to the work presented in [19]. PMDS ink can be prepared by first mixing the base with the curing agent of Sylgrad 184 in a ratio of 10:1 (base:curing agent) by weight, then diluting it with toluene 1:5 (PDMS:toluene) by volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dimatix inkjet printer requires a fluid with viscosity between 10–12 cP at jetting temperature; therefore, the mixture is diluted according to the work presented in [19]. PMDS ink can be prepared by first mixing the base with the curing agent of Sylgrad 184 in a ratio of 10:1 (base:curing agent) by weight, then diluting it with toluene 1:5 (PDMS:toluene) by volume.…”
Section: Methodsmentioning
confidence: 99%
“…While these approaches have resulted in conductive patterns on stretchable substrates, they did not succeed in fabricating stretchable circuits; as the printed patterns could not withstand even minimal elongation. The inkjet printing approach presented in [19] has resulted in the fabrication of conductive bendable circuits on silicon rubber. However, these flexible circuits are not wearable; as they cannot sustain large stretching actions which are required when placing them on non-planar surfaces [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, IJP sensor showed high accuracy at different postures. Firstly, the skin-like characteristics of the PDMS surface allow the IJP sensor to closely attach to the body surface and follow the topographical changes [34,35]. Secondly, the polymer-based strain gauge sensors are very sensitive (gauge factor > 100) compared with typical strain gauge (2 ≤ gauge factor ≤ 5).…”
Section: Rr Measurements At Different Body Posturesmentioning
confidence: 99%
“…Besides, stencil printing and screen printing are employed to pattern features that do not require high complexity and superfine resolution [ 19 , 20 , 21 ]. With the development of additive manufacturing, direct printing emerges as an alternative to the conventional subtractive patterning method [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Transfer printing generally means to transfer functional materials from one substrate to another.…”
Section: Patterning Techniquesmentioning
confidence: 99%
“…Patterning the conductors is one of the key techniques for the successful fabrication of stretchable electronic devices. The common patterning techniques for stretchable conductors include lithography [ 17 , 18 ], screen/stencil printing [ 19 , 20 , 21 ], direct printing [ 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and transfer printing [ 32 , 33 , 34 ]. The patterning methods used in wafer-based electronics have also been adopted in stretchable electronics.…”
Section: Introductionmentioning
confidence: 99%